Drugs Based on NMDAR Hypofunction Hypothesis in Schizophrenia - Wu, Qiongqiong; Huang, Jing; Wu, Renrong (Frontiers in Neuroscience, 2021)
Treatments for negative symptoms and cognitive dysfunction in schizophrenia remain issues that psychiatrists around the world are trying to solve. Their mechanisms may be associated with N-methyl-D-aspartate receptors (NMDARs). The NMDAR hypofunction hypothesis for schizophrenia was brought to the fore mainly based on the clinical effects of NMDAR antagonists and anti-NMDAR encephalitis pathology. Drugs targeted at augmenting NMDAR function in the brain seem to be promising in improving negative symptoms and cognitive dysfunction in patients with schizophrenia. In this review, we list NMDAR-targeted drugs and report on related clinical studies. We then summarize their effects on negative symptoms and cognitive dysfunction and analyze the unsatisfactory outcomes of these clinical studies according to the improved glutamate hypothesis that has been revealed in animal models. We aimed to provide perspectives for scientists who sought therapeutic strategies for negative symptoms and cognitive dysfunction in schizophrenia based on the NMDAR hypofunction hypothesis.